The Calculation and Thermal Coating Selection of Nano Satellite Steady State Temperature - Ahmad Fauzi (International Journal of Science, Engineering, and Information Technology, 2018)
At the beginning of the design phase of satellite, it is an important in order to consider the design of satellite’s thermal control system by analyzing the temperature that occurs in the space environment. This paper presented the analysis of coating thermal steady-state temperature calculation that occurs in the structure and solar panels of the satellite. Temperature calculation analysis without internal power dissipation satellite is performed in three cases with different of thermal coating, to determine whether the temperature scale in accordance with the allowable temperature. The calculation results are shown that by using the materials of 60% solar cells, 40% aluminum and 100% black paint (Case C) is the best choice of thermal coating materials selection and it will take the operating temperature between -107.82°C and 24.70°C. It’s still within the limits of allowable satellite’s operations.